From proteomics to biotechnology. using the resurrection plant eragrostis nindensis to genetically engineer drought tolerant crops - Van Der Pas, Llewelyn (Department of Molecular and Cell Biology, 2026)
Global climate change is increasingly putting pressure on finding innovative solutions to ensure future food security in particular to developing African nations. Of great relevance are regionally adapted crops, known as orphan crops, which tend to have very little economic value but can provide a source of alternative food security. Vegetative desiccation tolerance is a remarkable feat of selective evolution and is only present in a small number of angiosperms. The ability of some plants, such as Eragrostis nindensis to survive complete cellular water deficit provides an attractive model for discovery-based omics to not only understand the mechanisms involved in driving desiccation tolerance but to explore the feasibility of potential target genes for orphan crop improvement. The work presented herein was aimed at complementing a transcriptomic study using the same leaf tissue from that study to evaluate the changes from RNA to protein and to determine whether there were proteomic signatures that could differentiate the desiccation-tolerant non-senescent (NST) leaves from the desiccation-sensitive senescent (ST) leaves. The data presented here illustrate that several important metabolic pathways are significantly reprogrammed, that only a small subset of proteomic-matching transcripts were translated, and that proteomic differences between the NST and ST were noted despite their being significant similarities between the two in general oxidative and osmotic stress. For instance, the prevention of ferroptosis and accumulation of raffinose synthase and starch synthase in the NST exclusively illustrated that small and subtle increases in protein abundance are likely responsible for enabling resurrection in the NST and not in the ST, which we hypothesise here is likely due to sacrificing of ST upon rehydration as a means to act as a source of nutrition for the NST during resurrection. The study also focussed on functional characterisation of a heat shock 70 protein from E. nindensis as a target for genetic engineering. The selected EnHSP70 was shown to localise to the chloroplast and was able to undergo liquid-liquid phase separation in vitro in a protein concentration and polyethylene glycol dependent manner which could have broad impacts on its role in maintaining proteostasis. In Arabidopsis thaliana, overexpression of EnHSP70 resulted in a stunted germination phenotype whereas expression in BL21 Escherichia coli did not enhance tolerance towards salt or mannitol stress. Furthermore, incubation of EnHSP70 with lactate dehydrogenase did not confer improved thermotolerance. Taken together, the selected HSP70 from E. nindensis did not appear to be involved in stress response and is likely involved with general proteostasis. Lastly, a method for generating embryonic calli from Eragrostis tef is presented with the goal of using this developed protocol for the genetic improvement of the Ethiopian orphan crop.